Strength training versus stretching for improving range of motion: A systematic review and meta-analysis - Afonso, J.; Ramirez-Campillo, R.; Moscão, J.; Rocha, T.; Zacca, R.; Martins, A.; Milheiro, A. A..; Ferreira, J.; Sarmento, H.; Clemente, F. M. (healthcare, 2021)
(1) Background: Stretching is known to improve range of motion (ROM), and evidence has suggested that strength training (ST) is effective too. However, it is unclear whether its efficacy is comparable to stretching. The goal was to systematically review and meta-analyze randomized controlled trials (RCTs) assessing the effects of ST and stretching on ROM (INPLASY 10.37766/inplasy2020.9.0098). (2) Methods: Cochrane Library, EBSCO, PubMed, Scielo, Scopus, and Web of Science were consulted in October 2020 and updated in March 2021, followed by search within reference lists and expert suggestions (no constraints on language or year). Eligibility criteria: (P) Humans of any condition; (I) ST interventions; (C) stretching (O) ROM; (S) supervised RCTs. (3) Results: Eleven articles (n = 452 participants) were included. Pooled data showed no differences between ST and stretching on ROM (ES = -0.22; 95% CI = -0.55 to 0.12; p = 0.206). Sub-group analyses based on risk of bias, active vs. passive ROM, and movement-per-joint analyses showed no between-protocol differences in ROM gains. (4) Conclusions: ST and stretching were not different in their effects on ROM, but the studies were highly heterogeneous in terms of design, protocols and populations, and so further research is warranted. However, the qualitative effects of all the studies were quite homogeneous.